Inovasi Produk Olahan Kopi Dengan Cita Rasa Buah-Buahan Pada LMDH Watu Blorok KPH Mojokerto - Alwan Arif Fakhruddin; Ida Syamsu Roidah (Jurnal Kabar Masyarakat, 2023)
: This outreach activity aims to explore the potential and opportunities of innovation in fermented coffee products with fruits to support the development of the agricultural sector in Indonesia. Through socialization and providing materials, the community and LMDH groups in Jolotundo Village, Mojokerto Regency, were introduced to the concept of innovation in processed coffee products. Fermented coffee processing with fruits has become an attractive option for coffee enthusiasts seeking variety and uniqueness in the specialty coffee segment. The high demand for fermented coffee with fruits in the domestic and international markets indicates good sales potential. Through anaerobic fermentation techniques and the use of fruits, coffee processing becomes more engaging and allows for creative flavor exploration. Through discussions and evaluations, participants were able to understand and apply their knowledge of coffee product innovation in their farming practices. In conclusion, the innovation of fermented coffee products with fruits has the potential to generate innovative, distinctive, and diverse products in the coffee market. This development can increase farmers' income, expand the market, and support the growth of the agricultural sector in Indonesia.